Bullying in Schools 2004
DOI: 10.1017/cbo9780511584466.004
|View full text |Cite
|
Sign up to set email alerts
|

Is the direct approach to reducing bullying always the best?

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 14 publications
0
40
0
1
Order By: Relevance
“…This reminds us that bullying research and bullying prevention and intervention programs should not be confined to an individual approach focusing only on the personal characteristics of the bully and the victim, but also consider the social climate, group processes, classroom ecologies, and peer interactions at school (cf., Doll, Song, & Siemers, 2004;Galloway & Roland, 2004;Roland & Galloway, 2002;Salmivalli et al, 1996;Walcott et al, 2008). For example, a recent study has shown a negative correlation between high-rating perceptions of school moral atmosphere and children's tendency to blame the victim in hypothetical bullying scenarios (Gini, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This reminds us that bullying research and bullying prevention and intervention programs should not be confined to an individual approach focusing only on the personal characteristics of the bully and the victim, but also consider the social climate, group processes, classroom ecologies, and peer interactions at school (cf., Doll, Song, & Siemers, 2004;Galloway & Roland, 2004;Roland & Galloway, 2002;Salmivalli et al, 1996;Walcott et al, 2008). For example, a recent study has shown a negative correlation between high-rating perceptions of school moral atmosphere and children's tendency to blame the victim in hypothetical bullying scenarios (Gini, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Many items in the questionnaire were adapted from other instruments used in research exploring bullying, truancy and learner attitudes (Galloway and Roland 2004). The items on mobile phone use were adapted from the recent study by Porter et al (2016).…”
Section: Questionnaire Designmentioning
confidence: 99%
“…Дa би нaстaвник мoгao успeшнo дa дeлуje у прaвцу прeвeнциje и интeрвeнциje, вeoмa je вaжнo дa мeрe чиja сe примeнa прeпoручуje нe зaхтeвajу већи нaпoр приликoм њи-хoвe примeнe, нe oдузимajу прeвишe врeмeнa и дa могу бити интегрисанe у свaкoд-нeвнe вaспитнo-oбрaзoвнe aктивнoсти шкoлe (Colvin et al, 1998;Galloway & Roland, 2004;Vernberg & Gamm, 2003).…”
Section: прEвентивне и интервентне мEре и Aктивнoсти нA нивOу Oдeљeњaunclassified